'I pledge you!': Disability, monstrosity and sacrifice in Wytches. Issue 2 (1st December 2017) - Diamond, Aidan Dubhain
In the introduction to Freakery (1996), editor and disabilities scholar, Rosemarie Garland Thomson, charts a shift in the West's cultural perception of and relation to 'freaks', arguing that the extraordinary body once viewed with wonder became, over the course of the nineteenth century, a site of error. Michel Foucault ([1984] 2010) identifies the same trend on a broader scale, demonstrating that during the eighteenth and nineteenth centuries, certain populations – the mad, the criminal, the impoverished, the queer – were rewritten as a social disease blighting normative society. This social equation endures to this day; one has only to scan recent blockbusters to identify the monstrous body as evil, the deformed body as deficient and expendable and, by contrast, the able body as the practically un-killable hero. In this context, the thematic achievement of Scott Snyder et al.'s Wytches (2015) is notable for its refusal to adhere to this equation, and further for its articulation of a positive alternative to it. Wytches, a Gothic horror from the first page, inverts the Victorian equation of horror with madness and monstrosity. While the comic's eponymous antagonists are unquestionably monstrous, inhuman, and child-eating to boot, they are easily escaped and mainly act in response to the vile, selfish morality of the townsfolk they neighbour. This article first reviews theories of difference and othering as articulated by Rosemarie Garland Thomson and Michel Foucault, and expands understandings of 'freakery' and difference to include not just the corporeal but also the mental via Foucault, Sigmund Freud, Julia Kristeva, Max Nordau and Roy Porter. It then argues that Wytches' monstrous use of normative bodies against the dedicated rescue of its neuroatypical protagonist by abled and disabled characters alike, subtly and compellingly re-inscribing the freaked body not only as a heroic body but as a wondrous one, and argues fiercely against the long-standing social equation of difference and innate evil.